The sergeants speak: A language needs analysis of the Royal Netherlands Army - Prins, Martijn; Hagar, Trenton; de Graaff, Rick; Wilson, Jett (Dutch Journal of Applied Linguistics, 2025)
This mixed-method study identified the English language needs of Royal Netherlands Army sergeants to define language tasks and proficiency requirements. Participants for the Needs Analysis consisted of 62 former infantry sergeants and 11 subject matter experts. Data was collected through interviews and a questionnaire, and analyzed using a combination of open coding and descriptive statistics. Results detail when, where, and how soldiers use English. Twenty-six language tasks were identified, with a focus on military missions and multinational training exercises where using English was critical. Participants consider English essential in more senior roles, while experts recommend B1-level reading and listening, and A2-level speaking, with a focus on issuing orders. These results informed the proficiency requirements and the redesign of the English curriculum. This study serves as a model for needs analyses in specialized work environments.